Answer:
Step-by-step explanation:
tan Θ + tan 2Θ + √3 tan Θ tan 2Θ = √3
tan Θ + tan 2Θ = √3 - √3 tan Θ tan 2Θ
tan Θ + tan 2Θ = √3 ( 1 - tan Θ tan 2Θ)
(tan Θ + tan 2Θ) / (1 - tanΘ tan 2Θ) = √3
tan(Θ + 2Θ) = √3
tan 3Θ = tan (
) we know tan Θ = tan α; Θ = nΠ + α, n belongs to z
3Θ = nΠ + Π/3
Θ = nπ/3 + Π/9 for all n in Z
The inscribed angle theorem says that
![m\angle CAB=\dfrac12m\angle COB](https://tex.z-dn.net/?f=m%5Cangle%20CAB%3D%5Cdfrac12m%5Cangle%20COB)
Triangle AOC is isosceles because both AO and CO are radii of the circle and have the same length. This means angles CAO and ACO have the same measure and are congruent.
Angles ACO and COD are congruent because they form an alternating interior pair between the parallel lines AC and OD.
Taking all these facts together, we have
![m\angle COB=2m\angle COD](https://tex.z-dn.net/?f=m%5Cangle%20COB%3D2m%5Cangle%20COD)
and since angle COB is made up of angles COD and DOB, these angles must be congruent, and so the arcs they subtend (CD and DB, respectively) must also congruent.
Answer:
-4/f
Step-by-step explanation:
i hope this helps
hi
Answer:
What’s this called again? And do u possibly know the formula for this? I just need these elements to solve it... plz reply
Step-by-step explanation: